Study Of The Impact Of Mining Under Massive Roof At Datong Coal Mines, China (7e96e5f6-0b09-4bad-866d-2ffcd02d33be) - Song Yong Jin (International Conference on Ground Control in Mining, 1992)
The Jurassic coals at Datong are characterised by their strong, massive sandstone and conglomerate roofs which fail suddenly over large areas, crushing pillars and creating destructive windblasts, collapsed areas have exceeded 180,000m2 and windblasts have extended over one km underground and 200m on the surface and have been accompanied by subsidence troughs on the surface. Scientific analysis has researched premonitory signs of caving and the nature of windblasts leading to considerations of alternative mining methods and ways of dissipating the energy of windblasts to reduce their damage and danger.